‘Looking before and after’: Can simple eye tracking patterns distinguish poetic from prosaic texts? - Corcoran, Rhiannon; de Bezenac, Christophe; Davis, Philip (Frontiers in Psychology, 2023)
Introduction The study of ‘serious’ literature has recently developed into an emerging field called neurocognitive poetics that applies cognitive neuroscientific techniques to examine how we understand and appreciate poetry. The current research used eye-tracking techniques on a small sample of young adults to see if and how the reading of short pieces of poetry differed from the reading of matched prosaic texts. Methods With ‘proof of concept’ intentions reflecting arguments first proposed by 19th Century literary figures, there was a particular focus on the differences between the reading of poetry and prose in terms number and frequency of fixations and regressive eye movements back and forth within the texts in this two-by-two experimental design (poetry vs. prose x need vs. no need for final line reappraisal). Results It was found that poetic pieces compared to prosaic pieces were associated with more and longer fixations and more regressive eye movements throughout the text. The need to reappraise meaning at the prompt of a final line was only significantly associated with more regressive eye movements. Comparisons examining the 4 text conditions (poetic reappraisal, poetic non-reappraisal, prosaic reappraisal, and prosaic non-reappraisal) showed that the poetic reappraisal condition was characterised by significantly more regressive eye movements as well as longer fixations compared to the prosaic non-reappraisal condition. No significant correlations were found between self-reported literary familiarity and eye tracking patterns. Discussion Despite limitations, this proof-of-concept study provides insights into reading patterns that can help to define objectively the nature of poetic material as requiring slower reading particularly characterised by more and longer fixations and eye movements backwards through the texts compared to the faster, more linear reading of prose. Future research using these, and other psychophysiological metrics can begin to unpack the putative cognitive benefits of reading literary material.